Răspuns :
a 13-12+8+0=9
b) 10+36-35-3--8= 1
c) 13*6-8*5-11= 78- 40-11= 27
d) 25 +4* (2+3*35-93) -3*27 = 25+4* (2+105-93) - 111= 25+ 4* 14-111= 25+56-111=81-111=-30
e) (2*6*2- 10)*2 -28= 14*2-28=28-28=0
b) 10+36-35-3--8= 1
c) 13*6-8*5-11= 78- 40-11= 27
d) 25 +4* (2+3*35-93) -3*27 = 25+4* (2+105-93) - 111= 25+ 4* 14-111= 25+56-111=81-111=-30
e) (2*6*2- 10)*2 -28= 14*2-28=28-28=0
a)1+8=9 b)46-32-8=6 c) 13*6-8*5-11= 78- 40-11= 27
d) 25 +4* (2+3*35-93) -3*27 = 25+4* (2+105-93) - 111= 25+ 4* 14-111= 25+56-111=81-111=-30 e) (2*6*2- 10)*2 -28= 14*2-28=28-28=0
d) 25 +4* (2+3*35-93) -3*27 = 25+4* (2+105-93) - 111= 25+ 4* 14-111= 25+56-111=81-111=-30 e) (2*6*2- 10)*2 -28= 14*2-28=28-28=0